Removal of methylene blue (MB) dye from water and wastewater using acid-activated chicken bone in a batch adsorption process - Ghazala Muteeb; Khalid Ansari; Murat Eyvaz; Mohd Farhan; Mohammad Aatif; Dhiraj Agrawal; Mohamed El Oirdi; Mohammad Hadi Dehghani (Scientific Reports)
Abstract Sustainable wastewater management plays a vital role in mitigating environmental concerns. In this context, the present study evaluates the efficiency of methylene blue (MB) removal using a novel H3PO4-activated chicken bone adsorbent (CBAAC) in a batch adsorption process. The optimum conditions were determined at pH 7.5, contact time between 30 and 150 min, dye concentrations ranging from 10 to 50 mg/L, and adsorbent doses of 0.15–0.75 g/100 mL methylene blue (MB) dye solution. The maximum MB removal efficiency of 92.29% was achieved using 0.6 g of adsorbent after 90 min. CBAAC composite was characterized with FE-SEM to identify morphological structure, while FT-IR spectroscopy indicates the appearance of stretching functional bond groups. Response surface methodology (RSM) optimization using a central composite design (CCD) was evaluated showing a promising regression analysis of R2 = 0.9661. The research results demonstrated a well-defined Temkin adsorption isotherm (R2 = 0.9804), with a capacity for adsorption of 49.56 mg/g, closely followed by a pseudo-second-order kinetic model (R2 = 0.9997). The process was thermodynamically spontaneous and exothermic. A comprehensive Life Cycle Analysis (LCA) dealing with ten important parameters that resulted in the lowest global warming of 1.531 (kg CO2-eq.) and 5.047 MJ/kg, highlights the sustainable and effective use of CBAAC for the removal of organic dyes from wastewater.